Strongly Red-Emissive Molecular Ruby [Cr(bpmp)2]3+Surpasses [Ru(bpy)3]2+ - Reichenauer, Florian; Wang, Cui; Forster, Christoph; Boden, Pit; Ugur, Naz; Baez-Cruz, Ricardo; Kalmbach, Jens; Carrella, Luca M.; Rentschler, Eva; Ramanan, Charusheela; Niedner-Schatteburg, Gereon; Gerhards, Markus; et al. (Journal of the American Chemical Society, 2021)
Gaining chemical control over the thermodynamics and kinetics of photoexcited states is paramount to an efficient and sustainable utilization of photoactive transition metal complexes in a plethora of technologies. In contrast to energies of charge transfer states described by spatially separated orbitals, the energies of spin-flip states cannot straightforwardly be predicted as Pauli repulsion and the nephelauxetic effect play key roles. Guided by multireference quantum chemical calculations, we report a novel highly luminescent spin-flip emitter with a quantum chemically predicted blue-shifted luminescence. The spin-flip emission band of the chromium complex [Cr(bpmp)2]3+ (bpmp = 2,6-bis(2-pyridylmethyl)pyridine) shifted to higher energy from ca. 780 nm observed for known highly emissive chromium(III) complexes to 709 nm. The photoluminescence quantum yields climb to 20%, and very long excited state lifetimes in the millisecond range are achieved at room temperature in acidic D2O solution. Partial ligand deuteration increases the quantum yield to 25%. The high excited state energy of [Cr(bpmp)2]3+ and its facile reduction to [Cr(bpmp)2]2+ result in a high excited state redox potential. The ligand's methylene bridge acts as a Brønsted acid quenching the luminescence at high pH. Combined with a pH-insensitive chromium(III) emitter, ratiometric optical pH sensing is achieved with single wavelength excitation. The photophysical and ground state properties (quantum yield, lifetime, redox potential, and acid/base) of this spin-flip complex incorporating an earth-abundant metal surpass those of the classical precious metal [Ru(α-diimine)3]2+ charge transfer complexes, which are commonly employed in optical sensing and photo(redox) catalysis, underlining the bright future of these molecular ruby analogues.
CRIS-Team Scopus Importer:2023-03-27